Ответ:
[tex]3(4x - 3) - 2(2 - x) = 2(4x - 3) \\12x-9-2\left(2-x\right)=2\left(4x-3\right) \\12x-9-4+2x=2\left(4x-3\right) \\12x-13+2x=2\left(4x-3\right) \\14x-13=2\left(4x-3\right) \\14x-13=8x-6 \\14x-13-8x=-6 \\6x-13=-6 \\6x=-6+13 \\6x=7 \\x = \frac{7}{6} = 1\frac{1}{6} [/tex]
2*(3х-2)-3*(4х-3)=2-4х
6x-4-12x+9=2-4x
-6x+5=2-4x
-6x+4x=2-5
-2x=-3
х=(-3):(-2)
х=1,5
Ответ: х=1,5
Пошаговое объяснение:
Изи.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]3(4x - 3) - 2(2 - x) = 2(4x - 3) \\12x-9-2\left(2-x\right)=2\left(4x-3\right) \\12x-9-4+2x=2\left(4x-3\right) \\12x-13+2x=2\left(4x-3\right) \\14x-13=2\left(4x-3\right) \\14x-13=8x-6 \\14x-13-8x=-6 \\6x-13=-6 \\6x=-6+13 \\6x=7 \\x = \frac{7}{6} = 1\frac{1}{6} [/tex]
Ответ:
2*(3х-2)-3*(4х-3)=2-4х
6x-4-12x+9=2-4x
-6x+5=2-4x
-6x+4x=2-5
-2x=-3
х=(-3):(-2)
х=1,5
Ответ: х=1,5
Пошаговое объяснение:
Изи.